Fat mass- and obesity-associated genotype, dietary intakes and anthropometric measures in European adults: the Food4Me study. Issue 3 (1st December 2015) - Livingstone, Katherine M.; Celis-Morales, Carlos; Navas-Carretero, Santiago; San-Cristobal, Rodrigo; Forster, Hannah; O'Donovan, Clare B.; Woolhead, Clara; Marsaux, Cyril F. M.; Macready, Anna L.; Fallaize, Rosalind; Kolossa, Silvia; Tsirigoti, Lydia; et al.
Abstract: The interplay between the fat mass- and obesity-associated ( FTO ) gene variants and diet has been implicated in the development of obesity. The aim of the present analysis was to investigate associations between FTO genotype, dietary intakes and anthropometrics among European adults. Participants in the Food4Me randomised controlled trial were genotyped for FTO genotype (rs9939609) and their dietary intakes, and diet quality scores (Healthy Eating Index and PREDIMED-based Mediterranean diet score) were estimated from FFQ. Relationships between FTO genotype, diet and anthropometrics (weight, waist circumference (WC) and BMI) were evaluated at baseline. European adults with the FTO risk genotype had greater WC ( AA v . TT : +1·4 cm; P =0·003) and BMI (+0·9 kg/m 2 ; P =0·001) than individuals with no risk alleles. Subjects with the lowest fried food consumption and two copies of the FTO risk variant had on average 1·4 kg/m 2 greater BMI ( P trend =0·028) and 3·1 cm greater WC ( P trend =0·045) compared with individuals with no copies of the risk allele and with the lowest fried food consumption. However, there was no evidence of interactions between FTO genotype and dietary intakes on BMI and WC, and thus further research is required to confirm or refute these findings.